Polyphenol deposition in leaf hairs of Olea europaea (Oleaceae) and Quercus ilex (Fagaceae) (AMERICAN JOURNAL OF BOTANY, 1998)
The subcellular localization (cytoplasm, vacuoles, cell walls) of polyphenol compounds during the development of the multicellular nonglandular leaf hairs of Olea europaea (scales) and Quercus ilex (stellates), was investigated. Hairs of all developmental stages were treated with specific inducers of polyphenol fluorescence, and the bright yellow-green fluorescence of individual hairs was monitored with epifluorescence microscopy. During the early ontogenetic stages, bright fluorescence was emitted from the cytoplasm of the cells composing tie multicellular shield of the scales of O. europaea. Transmission electron micrographs of the same stages showed that these cells possessed poor vacuolation and thin cell walls. The nucleus of these cells may be protected against ultraviolet-B radiation damage. The progressive vacuolation that occurred during maturation was followed by a shifting of the bright green-yellow fluorescence from the perinuclear region and the cytoplasm to the cell walls. The same trends were observed during the development of the nonglandular stellate hairs of Quercus ilex, in which maturation was also accompanied by a considerable secondary thickening of the cell walls. Despite the differences in morphology, high concentrations of polyphenol compounds are initially located mainly in the cytoplasm of the developing nonglandular hairs, and their deposition on the cell walls rakes place during the secondary cell wall thickening. These structural changes during the development of the leaf hairs make them a very effective barrier against abiotic (UV-B radiation) and probably biotic (pathogenic) stresses.